Effect of Ethnicity on the Females' Brain Weight in Northern Iran - Kamran Heidari; Mehrdad Jahanshahi; Mohammad Jafar Golalipour (Negah Institute for Scientific Communication, 2014)
Introduction: Brain weight and cranial capacity are important parameters in the study of racial/ ethnic differences. This study was done to determine the effect of ethnicity on the female's brain weight in Northern Iran. Methods: Brain weight was estimated using linear (Lee-Pearson's) formula in 410 normal 17-20 year old (207 native Fars and 203 Turkman) females in northern Iran. Dimensions of the head measured with spreading caliper and auricular head spanner. Results: The mean±SD of brain weight in native Fars and Turkmen females were 1258.33±130 and 1270.17±124 grams and 1215, respectively. Conclusion: This study showed that Brain weight in Turkmen's was higher than native Fars females.